Evaluation of Raman microscopy for the detection of additional monosodium glutamate in dry soup mix - Cebi, N.; Ozturk, T.; Dogan, C. E.; Sagdic, O. (CODON PUBLICATIONS, 2020)
This article presents Raman chemical mapping application for the detection of adulterant monosodium glutamate (MSG) in dry soup mix. MSG may cause various damages to the health of people. Therefore, there are legal regulations for this compound both in Turkish Food Codex and European Union Directives. Most of the times, the main problem is that MSG is added into dry soup products without declaration on the label. Food control mechanisms need effective and real-time monitoring methods to check the reliability of the product labels in order to maintain food safety and alleviate public doubts. In this study, MSG was added into dry soup mix at a concentration (w/w) of 0.1, 0.2, 0.4 and 0.6% and chemical maps were obtained using multivariate data analysis techniques such as direct classical least squares (DCLS) component analysis. MSG was successfully detected and spectral and spatial distribution of the MSG within the commercial and laboratory-prepared dry soup samples was accomplished, with a detection limit of 0.1%. The results obtained were confirmed by a robust liquid chromatography-tandem mass spectrometry (LC-MS/MS) technique.
Keywords: monosodium glutamate; Raman; mapping; imaging; DCLS; ACID; SPECTRA; MSG; DIFFERENTIATION; SAMPLES; SAFETY; Food Science & Technology